Effect of tree cover and tree species on microclimate and pedestrian comfort in a residential district in Iran. (July 2020) - Teshnehdel, Saeid; Akbari, Hassan; Di Giuseppe, Elisa; Brown, Robert D.
Abstract: According to the challenge of global warming, trees play an effective role in reducing heat islands and improving thermal comfort. In this study, the impact of urban greening on microclimate and pedestrian comfort is studied using ENVI met v4 for a residential district in Tabriz, Iran. In-situ measurements of air temperature and relative humidity have been preliminary performed on ten points in the studied site and collected data used to successfully validate the model. Four scenarios with different trees species and patterns were simulated during typical summer and winter days, to assess benefits and disadvantages during different seasons, in terms of air temperature (Ta) and relative humidity (RH), mean radiant temperature (Tmrt) and physiologically equivalent temperature (PET). Result showed that the best scenario provides great summer cooling without compromising winter comfort. In summer Ta and Tmrt are decreased by respectively 0.29 °C and 20.04 °C; while in winter, they reach respectively 6.92 °C and 13.22 °C, compared the reference scenario characterised by 6.28 °C (Ta) and 23.47 °C (Tmrt). These results in a summer PET improvement from 34.92 °C to 26.16 °C, thus moving from an original hot thermal sensation to a slightly warm one. Based on the outcomes of the study, it is possible to provide useful design recommendation for urban adaptation plans. Highlights: Four scenarios with different trees species and patterns were simulated during typical summer and winter days. From a qualitative point of view, trends highlight a good agreement among observed and predicted data. Urban greening design can reduce mean radiant temperatures by 20.04 °C. The change of RH both in summer and winter is modest and can be considered irrelevant for environmental comfort.